Entrepreneurial self-efficacy in Italy: an empirical study from a gender perspective - Spagnoli, P. (2017)
Entrepreneurial self-efficacy (ESE) is a key factor for the promotion of entrepreneurship. Literature emphasizes the need for and, indeed, recommends a gender perspective in the study of ESE. The aim of this study is twofold: To begin analyzing some of the psychometric properties of the McGee, Peterson, Mueller, and Sequeira (2009) ESE scale in the Italian context, and to explore the gender differences in the ESE levels in an Italian sample of entrepreneurs and non-entrepreneurs. Confirmatory factor analysis, multigroup confirmatory factor analysis and a 2 × 2 MANOVA were conducted. The results support the possible use of McGee et al.'s ESE scale in the Italian context. Furthermore, they reveal that the gender difference in the sample of non-entrepreneurs is greater than in the entrepreneur sample. The main practical implication is that women entrepreneurs should receive specific training both before and after creating a new venture.